Normative Vacuum and Implementation Obstacles of the Undercover Buy Technique in Combating Illicit Narcotics Trafficking in Bandung City, Indonesia - Sidik Sugiharto; Ujuh Juhana (Westscience Press, 2026)
The undercover buy technique is an indispensable investigative instrument for uncovering organized narcotics trafficking networks, yet its regulation within Indonesian positive law contains critical normative gaps that compromise both enforcement effectiveness and the rule of law. This study aims to juridically analyze the regulation of the undercover buy technique under Law No. 35 of 2009 on Narcotics and the newly enacted Code of Criminal Procedure (Law No. 20 of 2025,